Legal support of human life outside the Earth in the conditions of rapid space exploration - Tienieshev, Viacheslav; Аntoshkiv Alina (Actual problems of law (Aktual’ni problemi pravoznavstva), 2021)
The article examines the gaps in the legislation in the field of space relations, analyzes the current international agreements and examines the problems of their practical application. The necessity of legislative regulation of future space colonization, mining, protection of subjects of space relations, and possible consequences of ignoring these issues have been studied. States and multinational companies have their own desire for outer space. Elon Mask hopes to use his "SpaceX" (a private enterprise working in the field of space transport construction) to launch a human colony on the planet Mars. Amazon owner Jeff Bezos, the world’s largest circulating company that sells goods and services, also notes the colonization of space. In this regard, it is important to find new possible directions and improve existing ways to address current space and legal issues to ensure the progressive development of international and national space law. The main objectives of space law are to ensure a rational, responsible approach to the study and use of outer space for the benefit and in the interests of all mankind. To this end, space law addresses a wide variety of issues, such as military activities in outer space, conservation of space and the Earth’s environment, liability for damage caused by space objects, settlement of disputes, protection of national interests, rescue of astronauts, exchange of information on potential dangers. in outer space, the use of space technology and international cooperation. The main treaties governing space today seem weak. This is due to the non-compliance and relevance of international agreements on space activities to modern scientific development and significant space achievements. Using the gaps in the field of international space law, many leading countries of the world are independently developing areas of legal support for space relations. For example, the staff of the Dubai International Financial Center of the UAE proposes in 2021 to reform the national judicial system and create a "judicial support network" that can handle complex commercial agreements related to space. Such an approach would destroy the established system of international law. In order to maintain peace and security and achieve a high degree of cooperation for the benefit of mankind as a whole, it is necessary to immediately begin work on the UN platforms to prepare and adopt comprehensive international legal acts to regulate human activities in space, taking into account experience in this field.